Pengembangan Media Pembelajaran Pencak Silat Siswa Tunarungu Di Kabupaten Grobogan - Ulya Sekar Arumdhani; Ipang Setiawan; Mugiyo Hartono; Bhayu Billiandri (Indonesian Journal for Physical Education and Sport, 2024)
The development of pencak silat learning media is a media development to provide movement experience for deaf students to perform some basic movements in pencak silat. The lack of learning media in Grobogan Regency SLB does not become an excuse for the obstruction of the PE learning process at school for deaf students. This research uses R&D (research and development) development research. The development model used is ADDIE (analyse, design, development, implementation, evaluation). As well as, data collection using interview techniques, observation, documentation, and questionnaires. This research produces pencak silat learning media in the form of bags and hanging balls and supports that have been modified for deaf students. Based on the validation that has been done by media experts, it produces an average score of 95.8% and martial arts subject experts produce 96.8% in the ‘Very Good’ category. The results of small-scale field trials showed an average score of 97.3% in the ‘Very Good’ category and large-scale trials showed an average score of 97.6% in the ‘Very Good’ category. The conclusion of this study is that the development of learning media for pencak silat for deaf students reached the ‘Very Good’ category. Thus, the martial arts learning media products made by researchers are suitable for use in the learning process of deaf students'martial arts.